A New Approach to Empirical Investigation under Persistence, Endogeneity, and Heterogeneity for South Asia: Understanding of the Deeper Dynamics of the Relationship Among Income Disparity and Education - Munir, Faisal; Farooq, Fatima; Ahmad, Rashid; Rafeeq, Rifat (iRASD Journal of Economics, 2023)
This study experimentally explores the income disparity and education expansion association, that is, strengthening average years of schooling and shrinking schooling disparity, using a sample of South Asian nations from 1980 to 2015 with five years regular interval. South Asian economies are frequently investigated in the literature on disparity, and the World Development Report primarily focused on educational problems and expounded on a high level of learning disparity in South Asia. The dynamic panel Arellano-Bond Following current work, the study employs GMM estimating approaches to report questions of ‘persistence and endogeneity’; we notice a huge, optimistic, statistically important, and steady average years of schooling and income disparity association in South Asian economies. The average years of education are positively correlated with income disparity, which is consistent with constant or rising returns to more years of education. We also find a slight and not necessarily statistically significant positive association among educational expense and income disparity, as well as a statistically significant unfavorable relationship among income disparity and immature associates. Statistical tests show that our identification instruments and vibrant indicators are both reliable. The increase of schooling is likely to continue lowering disparity, according to policy worries. This function will decline as nations grow, but it might be strengthened by putting more effort into lowering educational quality disparities.